PROXY WAR AND INDONESIA’S NATIONAL SECURITY: VICTORIA CONCORDIA CRESCIT - Hidayat, Safril (Jurnal Pertahanan dan Bela Negara, 2017)
Abstract – Proxy war have occurred since ancient times until now which is conducted by the major state powers by using state actors or non-state actors. The national interests of the big countries with objective of the struggle for power and the power of influence in affecting international relations. Proxy war has motives and hard power and soft power approaches to achieve their goals. Indonesia is safeguarding its national security in dealing with the proxy war strategy against disintegration attempts, thus it can be eliminated and the integration of the Unitary Republic of Indonesia will remains intact. To safeguard the integration of the nation, Indonesia must take a counter proxy measures. This article uses qualitative approach with data from reference sources and literature related to the proxy war. The validity and reliability of the data was tested by triangulation reference. The study shows that the counter proxy war conducted by maintaining Unity in Diversity which resemble the Opus Dei upon Indonesia, implementing policies and avoiding materialistic for the benefit of people (pro bono), and keeping the harmony of Indonesia. Keywords: Proxy war, proxy war motives, national security, counter proxy war.